Inhibition of Granuloma Triglyceride Synthesis Imparts Control of Mycobacterium tuberculosis Through Curtailed Inflammatory Responses - Dawa, Stanzin; Menon, Dilip; Arumugam, Prabhakar; Bhaskar, Akash Kumar; Mondal, Moumita; Rao, Vivek; Gandotra, Sheetal (Frontiers in Immunology, 2021)
Lipid metabolism plays a complex and dynamic role in host-pathogen interaction during Mycobacterium tuberculosis infection. While bacterial lipid metabolism is key to the success of the pathogen, the host also offers a lipid rich environment in the form of necrotic caseous granulomas, making this association beneficial for the pathogen. Accumulation of the neutral lipid triglyceride, as lipid droplets at the cellular cuff of necrotic granulomas, is a peculiar feature of pulmonary tuberculosis. The role of triglyceride synthesis in the TB granuloma and its impact on the disease outcome has not been studied in detail. Here, we identified diacylglycerol O-acyltransferase 1 (DGAT1) to be essential for accumulation of triglyceride in necrotic TB granulomas using the C3HeB/FeJ murine model of infection. Treatment of infected mice with a pharmacological inhibitor of DGAT1 (T863) led to reduction in granuloma triglyceride levels and bacterial burden. A decrease in bacterial burden was associated with reduced neutrophil infiltration and degranulation, and a reduction in several pro-inflammatory cytokines including IL1β, TNFα, IL6, and IFNβ. Triglyceride lowering impacted eicosanoid production through both metabolic re-routing and via transcriptional control. Our data suggests that manipulation of lipid droplet homeostasis may offer a means for host directed therapy in Tuberculosis.